ANALYSIS CAPACITY OF WATERWAY IN ANEKA ELOK EAST JAKARTA - Imamuddin, Mohammad Imam; Laraswati, Laraswati (Universitas Ibn Khaldun Bogor, 2021)
The problem of flooding in Aneka Elok, which is located in the city of East Jakarta, is still a matter of concern, because every rainy season it is always routinely flooded. The catchment area in this study is 0,75 km2 has a primary waterway that flow along the Aneka Elok area which flows northward to the reservoir and pump house. The reservoir in Aneka Elok area is located on an area of 32.000m2, is able to accommodate a flood debit of 225m3 with an average depth of 4m. And has a pump capacity of 1000 liters/second as much as 2 units. With the current capacity of the reservoir and pump capacity, it is still not able to overcome the debit flood existing. This study aims to determine the existing debit in Aneka Elok area according to the return period of 5 years and 25 years, the debit flood existing in the research area, so that it can analyze the required waterway cross section and ideal pump capacity. With a return period of 5 years, the rainfall insensity of I5 is 91,95 mm/hour to calculate the debit flood due the rain and compared to the debit existing flood, it is found that thecapacity of the existing waterway at C1-C2, C4-C9 and C11 is not sufficient to accommodate the current debit flood, so it is necessary to modify the waterway dimension. With a return period of 25 years, the rainfall insensity I25 is 169,66 mm/hour to calculate the pump capacity, it is found that current capacity is still not sufficient so that it is necessary to increase the pump capacity from 2 m3/s to 3,5 m3/s to accelerate water flow.